Studying Properties of Prospective Biologically Active Extracts from Marine Hydrobionts - Olga P. Chzhu; Daredzhan E. Araviashvili; Irina G. Danilova (Ital Publication, 2020)
Biologically active substances (BAS) extracted from marine hydrobionts are characterized by high diversity and efficiency. They are represented by carotenoids, phospholipids, saponins and other compounds possessing high antioxidant (AOA), antitumor, immunomodulatory, radioprotective, and hypolipidemic activities. Because of extremely high marine BAS activity, the BAS dose necessary for treatment and prevention of many diseases is very small. The aim of present work was to assess biological properties of BAS complexes extracted from Black Sea marine inverterbrates for their following using in pharmacological preparations including liposomal drug delivery. BAS complexes were extracted from marine invertebrate tissues by two-phase extraction in combination with ultrasonication. Antioxidant activity of BAS extracts was determined with potassium permanganate discoloration method in an aqueous sulfuric acid medium. Antimicrobial activity was investigated by germination of BAS extracts. BAS influence on lymphocyte proliferative activity was studied with help of cytogenetic analysis. In this paper, the assessment of antioxidant, antimicrobial and mitogenic activities of biologically active complexes extracted from marine invertebrate tissues is presented. BAS properties in the oil and alcohol-water phases are compared. For the first time BAS complexes from Black Sea invertebrates are extracted by the resource-light method of two-phase extraction in combination with ultrasonication. Conditions for obtaining BAS extracts with optimal characteristics are proposed.